THE PROBLEM OF PERIODIZATION OF PEDAGOGICAL PERSONNEL STUDY - Rozman, Iryna (Mountain School of Ukrainian Carpaty, 2019)
The article is devoted to the analysis of the problem of periodization of the research of pedagogical personnel. The theoretical and methodological approaches of Ukrainian and foreign scientists to the periodization of the development of historical and pedagogical science, which are based in general on the technologies of using the methodological tools of historical science, are determined. The role, significance, potential of comparative – historical, comparative, and other methods that are used in studies devoted to life and various directions of creative and social activity of pedagogical personalities are described. Two methodologically important approaches are found for conducting studies in the field of pedagogical biography, which are related to the study of a person in a universal coordinate system: a synchronous system, projecting its analysis in a specific time period and diachronic, projecting the study of personalities in a time «vertical». Disadvantages of periodization as an instrument and means of scientific and cognitive activities are shown; the ways and possibilities of their minimization and increase of the scientific and heuristic efficiency of the periodization method are determined in the studied periods (stages) of the life path of the pedagogical personalities. The article substantiates the position according to which the correct application of methodological tools allows to avoid various manifestations of dichotomy (illicit division) in pedagogical and biographical research.